Competitiveness of Indonesian Coffee Commodities in Global Market - Erlambang Budi Darmanto; Suhartono Suhartono; Yunita Satya Pratiwi; Moh. Adenan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The scope of this research includes international trade in coffee commodities using the Harmonized System (HS) code 0901. The method used in this research uses Revealed Comparative Advantage (RCA) and Trade Specialization Index (ISP). RCA method, the four largest coffee exporting countries in Indonesia have an average value of 3.10. These values ​​mean that Indonesia has a strong comparative advantage but is still below Colombia, Brazil, and Vietnam. Based on ISP analysis, the position or stage of development of the Indonesia’s coffee trade with a value of 0.88. This indicates that the coffee commodity is at the fourth stage or maturity stage. Indonesian coffee is already at the stage of standardizing the technology used and shows that Indonesia as a coffee exporter in the global market.